Validity and reliability of an assessment instrument of track start in swimming - Fabrício Madureira; Thábata V.B. Gomes; Thiago A.C. Oliveira; Andrea M. Freudenheim; Umberto C. Corrêa (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. The development and validation of assessment instruments are essential procedures for any professional intervention, including in physical education and sports contexts. This study aimed to provide a component-based assessment instrument for track start in swimming. It refers to the act of starting the competitive swim by diving into the water from a raised block (platform) at the edge of the pool.